STRATEGIC TRAJECTORIES: AN IN-DEPTH EXPLORATION OF THE COMPLEX LANDSCAPE OF HIGHER EDUCATION IN INDONESIA - Sundoro; Nawang Kalbuana; Catra Indra Cahyadi (International Journal of Teaching and Learning, 2024)
This research presents a thorough and nuanced exploration of Indonesia's intricate and multifaceted landscape of higher education. The primary objective is to discern and illuminate strategic trajectories that have the potential to profoundly shape the future trajectory of the nation's academic institutions. Employing a meticulous approach, the study critically scrutinizes pivotal aspects, including key trends, challenges, and policy outcomes, offering profound insights into the dynamic forces that influence the higher education sector. Through a comprehensive analysis and an exhaustive literature review, this research skillfully navigates the complex interplay of internationalization, technological transformation, and the implementation of policies within the higher education realm of Indonesia. The study delves into the subtleties and complexities inherent in these dynamics, providing a rich understanding of how these factors intersect and influence the overarching landscape of higher education. Furthermore, the research goes beyond surface-level examination, emphasizing the need for a strategic and forward-thinking approach. The implications for future research are thoroughly discussed, underscoring the imperative for longitudinal studies that can provide sustained insights into the impact of evolving trends and policy changes over time. The call for exploring innovative pedagogical approaches reflects a proactive stance toward addressing the evolving needs of diverse student populations. Additionally, the research advocates for a deeper understanding of the intricate impact of internationalization on local institutions, urging scholars to unravel the nuanced implications of global influences on the indigenous higher education framework.